2018
DOI: 10.1016/j.contraception.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Provision of medical abortion by midlevel healthcare providers in Kyrgyzstan: testing an intervention to expand safe abortion services to underserved rural and periurban areas

Abstract: Success in scaling up midwife/nurse provision of medical abortion in Kyrgyzstan will require registration of mifepristone-misoprostol, regulations permanently allowing midwife/nurse provision, strengthened procurement and distribution systems to prevent stockouts of supplies, preservice training of midwives/nurses and their involvement in district level supervision, monitoring and reporting, and support from supervisors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The same nurses had a moderate agreement with physicians diagnosing incomplete abortions and ongoing pregnancy. A nonrandomised implementation study of 32 nurses and midwives who provided medical termination to 554 women across four remote services in Kyrgyzstan found that there was a high level of complete abortions with no adverse events or safety issues and a high level of patient satisfaction (Johnson et al, 2018). A multicentre randomised controlled equivalence trial of 1,094 women with incomplete first‐trimester abortions in Kenya found that women who were administered misoprostol by midwives to complete their abortions had slightly better outcomes than when administer by physicians (94.8% compared with 94.3%) (Makenzius et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The same nurses had a moderate agreement with physicians diagnosing incomplete abortions and ongoing pregnancy. A nonrandomised implementation study of 32 nurses and midwives who provided medical termination to 554 women across four remote services in Kyrgyzstan found that there was a high level of complete abortions with no adverse events or safety issues and a high level of patient satisfaction (Johnson et al, 2018). A multicentre randomised controlled equivalence trial of 1,094 women with incomplete first‐trimester abortions in Kenya found that women who were administered misoprostol by midwives to complete their abortions had slightly better outcomes than when administer by physicians (94.8% compared with 94.3%) (Makenzius et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…We describe the included study characteristics in Table 2 (see Additional file 1 for further details). Included studies were conducted in eight countries -Bangladesh [36], Democratic People's Republic of Korea (DPRK) [45], Ethiopia [30], India [31,32,37,42], Kyrgyzstan [33], Nepal [29,32,35,40,41,43,44,46], Nigeria [32,38,39] and South Africa [34].…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…MA combination packs in India and Bangladesh made self-medication safer and more intuitive for women, expanding its access to local pharmacies [36,37]. Some primary care clinics were unequipped to manage MA complications, but all studies detailed referral systems to secondary or tertiary care [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Privacy in facilities is essential to creating a safe environment for women, especially in communities where abortions are strongly associated with shame and discrimination.…”
Section: Infrastructurementioning
confidence: 99%
See 1 more Smart Citation
“…Midwives provided drugs for medical abortion to 554 women in Kyrgyzstan, achieving a complete abortion rate of 97.8%, without reported complications. 22 …”
Section: Literature Reviewmentioning
confidence: 99%